EFEKTIVITAS MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMA NEGERI 1 PANDAAN - Ninin Dwi Novita; Muhammad Nur Hadi; Syaifullah (Universitas Yudharta Pasuruan, 2019)
This study aims to find the effectiveness of the application of the Problem Based Learning model in PAI learning at the top level to generate curiosity and enthusiasm for learning in the PAI learning process. The problem in this study is the awareness of students about the importance of learning PAI which is very lacking. The purpose of this study was to determine whether PAI learning using a problem based learning model with mind map methods and cooperative learning was more effective when compared to PAI learning which only used other conventional methods. The sample of this study was 89 students consisting of class XI MIA 1, XI MIA 5, MIA 7 and IS 3 which were taken randomly. With simple random sampling technique. Data collection is done using (1) Questionnaire method, which is a method for collecting data using statements, (2) Documentation Method, which is looking for data about things or variables in the form of notes, transcripts, books and so on. This study aims to (1) find out the application of the Problem Based Learning model for high school class XI on Islamic Education subjects, (2) find out the effectiveness of the Problem Based Learning model in increasing the learning motivation of high school class XI students in Islamic Education subjects, and ( 3) knowing the inhibiting factors and solutions in applying the Problem Based Learning model.This study uses a quantitative approach. The method used is field research with the design of the pretest and posttest control group design. With the results of the pretest and posttest questionnaire we used the t-test calculation by comparing the results of the t test with t table.